The Analysis of Historical Origin and Productiveness of Derivational Affixes in the Declaration of Independence of America (1776) - Sanita, Joan (Universitas Sanata Dharma, 2014)
This paper presents the analysis of historical origin and the productiveness of affixes (prefixes and affixes) that are found in the text Declaration of Independence. It focuses mainly on derivational affixes combining with the morpheme and also its derivation in the history of English. It also notes the frequency and distribution of the affixes in the text.The aim of this study is to reveal the derivational affixes in the Declaration of Independence together with its analysis related to the origin of the affixes. Three sources of guidance are used as a means to aid the identification the affixes. They are dictionaries, books, and online resources.The result of the study shows that there are eight prefixes and eighteen categories of suffixes found in the Declaration of Independence. Moreover, it is noticed that most of the derivational affixes are still used till nowadays. The frequent prefixes in the text are un-, dis-, and in-. Meanwhile, the common suffixes found are ion (-tion, ation) followed by –ence (-ance) and –ment together with –er /-or. It can be concluded that their productivity remains to be survived till present day though there are also some affixes that show declensions.Keywords: derivational affixes, Declaration of Independence